You just multiply the numerators of the fractions and the denominators of the fractions together, and then reduce the fraction to simplify it from that point on.
Answer:
2x^2 - 16x + 30
Step-by-step explanation:
Here, we want to get the composite function;
p•q(x)
All we have to do here is to replace the x value in p(x) by the totality of q(x)
we have this as ;
= 2(x-3)^2 - 4(x-3)
= 2(x^2 -6x + 9) - 4(x-3)
= 2x^2 -12x + 18 -4x + 12
= 2x^2 - 16x + 30
1.) 28-3x-4= 2x+12+x
2.) 24-3x= 3x+12
3.)24-6x=12
4.)-6x=-12
5.)x=2
Answer:
A= H<u>b B
</u>
2
Step-by-step explanation:
Q16- = A=75
cm
Q17- = A=10in
Q18- = A=70
Answer:
D is the answers for the question
Step-by-step explanation:
please mark me as brainlest